FACEBOOK LIVE-STREAMING: HOW IT AFFECT THE PURCHASE INTENTION OF GENERATION Y IN MALAYSIA? (Journal of Business Management and Accounting, 2022)
Today, people use social media for communicating and browsing the internet during their spare time. Additionally, people are using social media as a means of leisure during their free time. When Facebook launched its Facebook Live streaming application in 2016, the phenomenon created new opportunities for marketers. Recently, Facebook Live streaming is getting popular among companies in promoting their products and services. This research aims to investigate the factors that influence consumers’ purchase intention using Facebook Live streaming. The dependent variable of this study is the purchase intention whereas the independent variable is the attitude towards the broadcasters, interactivity, peer influence, perceived risk and product quality. There were 200 Generation Y respondents from whom information was collected via Facebook using a questionnaire. The result of the study showed that attitude and peer influence affect the consumer purchase intention when watching Facebook Live. This study gives marketers insight into improving their strategies in influencing consumer purchase intention when using Facebook Live streaming.